Algoritma Ant Colony Optimization (ACO) untuk Pemilihan Jalur Tercepat Evakuasi Bencana Gunung Lokon Sulawesi Utara - Johan Reimon Batmetan (AITI, 2016)
As one of the areas located on the ring of fire, North Sulawesi has a natural disaster threat level is high enough. Mount Lokon, located in the North Sulawesi region is an active volcano with fairly high seismic activity. Mount Lokon eruption disaster management such as casualty evacuation and early warning system towards the arrival of this eruption to be slow. This is caused by the difficulty of determining the fastest evacuation path resulting in many casualties. The purpose of this study was to determine the fastest track in the evacuation of the eruption of Mount Lokon. The method used is Ant-Colony Optimization is a method in computing, artificialintelligence and tried as one method of determining the shortest path effectively. The results obtained from this study is the Ant-Colony Algorithm method can be used to determine the fastest track in the evacuation process volcanic eruption where evacuation points and pathways that must be passed can be determined quickly and effectively in the evacuation process.